1972
DOI: 10.1136/jnnp.35.3.356
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic hypothalamotomy for behaviour disorders

Abstract: SUMMARY Posterior hypothalamotomy is a relatively simple stereotactic procedure. The radiological determination of the target and its physiological corroboration by electrical stimulation are accurate. The lesions have always been made in the site of maximum sympathetic response. In this respect, the cardiovascular changes (hypertension and tachycardia), which are always elicited from a more restricted area, are of particular importance. Depth recordings, however, have been less useful. Undesirable side-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
3

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 19 publications
1
19
1
3
Order By: Relevance
“…The results in this study could not be compared to information previously reported by Sano et al [13], Narabayashi and Uno [10], Kiloh et al [11] or Schvarcz et al [14], since the aforementioned researchers did not include sufficiently detailed information on their measuring instruments, side effects or appropriate methodology in their reports. In the past, the decision to modify patient behavior by neurosurgery has led to excesses and treatment errors.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The results in this study could not be compared to information previously reported by Sano et al [13], Narabayashi and Uno [10], Kiloh et al [11] or Schvarcz et al [14], since the aforementioned researchers did not include sufficiently detailed information on their measuring instruments, side effects or appropriate methodology in their reports. In the past, the decision to modify patient behavior by neurosurgery has led to excesses and treatment errors.…”
Section: Discussioncontrasting
confidence: 54%
“…In 1966, Sano et al [13] described the use of hypothalamotomy in 22 patients, with favorable outcome; mild complications were reported at a follow-up of 2 months to 3 years. In 1972, Schvarcz et al [14] reported hypothalamotomy in 11 patients without specifying the results or complications, with a follow-up of 6 months to 4 years.…”
Section: Introductionmentioning
confidence: 99%
“…245 As in the amygdala, lesions in the pHr have been used for the combination of epilepsy and aggressive behavior. 244,255 Modern application of DBS to the pHr has mostly been for cases of mental retardation combined with severe aggression, and thus few results have been reported. In the first of 2 cases in the literature, a 22-year-old patient with mental retardation and aggression received bilateral low-frequency stimulation (15 Hz) to the pHr, and at 18-month follow-up the patient's behavior was significantly improved.…”
Section: Aggressive Behaviormentioning
confidence: 99%
“…After surgery, 1 patient became seizure free, and reductions in seizure intensity and frequency were experienced by another 9 patients (41%) who were receiving the same or a smaller dosage of medications at more than 2 years of follow-up. 54 In the 1970s and 1980s, other groups repeated Sano's procedures for the treatment of aggressive behavior 7,44,57,60 or for indications such as "extreme" sexual behavior 20 and alcohol and drug addiction 20 and for the treatment of "erethic children. "…”
Section: Human Surgery: the Lesional Era And Neurophysiological Testingmentioning
confidence: 99%